The paradox of invisibility and the “absoluteness” of religion and morality - Nassehi, Armin (MAD, 2020)
The sociological study of the relationship between morality and religion has been conducted from points of view belonging to theoretical traditions which evidence deficiencies for the understanding of both terms. The present work aims to critically analyze some central aspects of these approaches and proposes to overcome their difficulties by exposing their paradoxes and blind spots. The paper concludes with recommendations for the sociological study of religion and morality in the context of a functionally differentiated society.